THE USE OF SOCIAL MEDIA TWITTER IN THE MAKING OF NOVEL (Study on Twitter Polls in the Making of Novel The Architecture of Love) - Winny Aisyah Amini; Basuki Agus Suparno; Subhan Afifi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2017)
In everyday life, Twitter as a communication media is used by most people to complete their interaction needs. A writer, Ika Natassa, had used Twitter as an extension media for storytelling. She had used it as a media in developing the world of literacy by combining technological advances with her expertise writing novel. The novel entitled ‘The Architecture of Love’ is the first book in the world which made by using social media Twitter. The purpose of this study is to explain how the role of Twitter polls feature as a medium of interaction of making novel and its marketing was. This research is qualitative. The method used in this research is descriptive study. The process of collecting data had obtained by observation, interview, and literature study. From the discussion of research results is concluded, that the interaction between Ika Natassa as a writer with her followers quite often, supported by other features in the media Twitter. Joint Action is required and the follower’s enthusiasm to determine the idea of each chapter of the story in each episode from beginning to end. According to the readers, the book ‘The Architecture of Love’ has a strong branding as a book that utilizes social media, because the uniqueness that was built on every episode when the poll took place. During the ‘airing’ period, the poll story has collected 19,535 poll participants, over 49,000 readers, and when posted also sold over 15,000 copies in just 2 months.